2021
DOI: 10.1038/s41598-021-93475-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping of lentil (Lens culinaris Medikus) prebiotic carbohydrates toward improved human health and crop stress tolerance

Abstract: Lentil, a cool-season food legume, is rich in protein and micronutrients with a range of prebiotic carbohydrates, such as raffinose-family oligosaccharides (RFOs), fructooligosaccharides (FOSs), sugar alcohols (SAs), and resistant starch (RS), which contribute to lentil's health benefits. Beneficial microorganisms ferment prebiotic carbohydrates in the colon, which impart health benefits to the consumer. In addition, these carbohydrates are vital to lentil plant health associated with carbon transport, storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Total RFO concentration of lentil cultivars varied from 4.5 to 5.5 moles 100 g –1 flour. Johnson et al (2021) found 7 to 31% variation for RFOs in lentil seeds from 143 accessions. Significant differences were observed between different years of lentil harvest.…”
Section: Raffinose Family Oligosaccharides Diversity In Cropsmentioning
confidence: 95%
“…Total RFO concentration of lentil cultivars varied from 4.5 to 5.5 moles 100 g –1 flour. Johnson et al (2021) found 7 to 31% variation for RFOs in lentil seeds from 143 accessions. Significant differences were observed between different years of lentil harvest.…”
Section: Raffinose Family Oligosaccharides Diversity In Cropsmentioning
confidence: 95%
“…especially within allergen-and gluten-free markets [7,37,38]. Our results indicate organic dry peas are rich in prebiotic carbohydrates (12.5-19.8 g/100 g), providing 63-99% of the RDA for adults (Table 5).…”
Section: Plos Onementioning
confidence: 67%
“…Due to the dietary nature of human metabolic disorders related to obesity, solutions will necessarily focus on a diet-i.e., a cup of pulses a day provides 13-15 g of prebiotic carbohydrates and a range of micronutrients [6,9,44]. Changing the levels of these prebiotic carbohydrates is possible by developing molecular markers for marker-assisted breeding with conventional breeding methods in pulse crops; however, genome-wide association mapping studies with diverse populations at several field locations are essential to avoid the yield and protein penalty by changing certain carbohydrates as a result of the quantitative nature of these nutritional traits [37,45]. Pulses crops, including dry pea, also known as "poor man's meat," are low in fat and provide significant quantities of dietary protein (20-25 g/100 g) and minerals [7,46].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…], barley ( Hordeum vulgare L.), cotton ( Gossypium hirsutum L.), and the model plant species Arabidopsis ( Tibbs Cortes et al, 2021 ). However, GWAS application in lentil is very limited with studies mainly restricted to traits such as carbohydrate, iron, zinc content, anthracnose, ascochyta, aphanomyces resistance, and agronomic traits ( Table 2 ; Singh et al, 2017a ; Khazaei et al, 2018 ; Kumar et al, 2019 ; Ma et al, 2020 ; Dadu et al, 2021 ; Gela et al, 2021a ; Johnson et al, 2021 ). GWAS studies are urgently needed in lentils to understand complex traits related to abiotic and biotic stress, plant development, and nutritional aspects.…”
Section: Genomic Innovations Reveal a New Genetic Landscape For Lenti...mentioning
confidence: 99%